Effects of Superheated Steam Treatment on the Allergenicity and Structure of Chicken Egg Ovomucoid - Ping-Wei Wen; Zong-Cai Tu; Yue-Ming Hu; Hui Wang (Foods, 2022)
The aim of this study was to explore the effects of an emerging and efficient heating technology, superheated steam (SS), on the allergenicity and molecular structure of ovomucoid (OVM). OVM was treated with 120–200 °C of SS for 2 to 10 min. The allergenicity (IgG/IgE binding abilities and cell degranulation assay) and molecular structure (main functional groups and amino acids modification) changes were investigated. The IgG-binding ability of OVM decreased and the releases of β-hex and TNF-γ were inhibited after SS treatment, indicating that the protein allergenicity was reduced. Significant increases in oxidation degree, free SH content and surface hydrophobicity were observed in SS-treated OVM. The protein dimer and trimer appeared after SS treatment. Meanwhile, obvious changes occurred in the primary structure. Specifically, serine can be readily modified by obtaining functional groups from other modification sites during SS treatment. Moreover, the natural OVM structure which showed resistance to trypsin digestion was disrupted, leading to increased protein digestibility. In conclusion, SS-induced OVM aggregation, functional groups and amino acids modifications as well as protein structure alteration led to reduced allergenicity and increased digestibility.